1996
DOI: 10.1111/j.1558-5646.1996.tb03911.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Indirect Mate Choice, Competition for Mates, and Coevolution of the Sexes

Abstract: Abstract.-When Darwin first proposed the possibility of sexual selection, he identified two mechanisms, male competition for mates and female choice of mates. Extending this classification, we distinguish two forms of mate choice, direct and indirect. This distinction clarifies the relationship between Darwin's two mechanisms and, furthermore, indicates that the potential scope for sexual selection is much wider than thus far realized. Direct mate choice, the focus of most research on sexual selection in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
155
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(162 citation statements)
references
References 92 publications
5
155
0
2
Order By: Relevance
“…Schaller et al (1985 and Pan et al (2001) reported that males occupy large home ranges that overlap several female and male home ranges, and that males engage in significant competition for females before and during each female's brief 3-day fertile period. Despite the clear role for intrasexual male competition, it is possible that female pandas exercise indirect choice (sensu Wiley and Poston 1996), where female behavior sets the stage for male-male competition. Female pandas advertise reproductive condition through scent beginning up to several weeks before the fertile period (Swaisgood et al 2000(Swaisgood et al , 2002(Swaisgood et al , 2004 and vocal signals (Charlton et al 2010), which may recruit males and incite competition, ensuring that the female mates with the best available male (Cox and Le Boeuf 1977).…”
Section: Introductionmentioning
confidence: 98%
“…Schaller et al (1985 and Pan et al (2001) reported that males occupy large home ranges that overlap several female and male home ranges, and that males engage in significant competition for females before and during each female's brief 3-day fertile period. Despite the clear role for intrasexual male competition, it is possible that female pandas exercise indirect choice (sensu Wiley and Poston 1996), where female behavior sets the stage for male-male competition. Female pandas advertise reproductive condition through scent beginning up to several weeks before the fertile period (Swaisgood et al 2000(Swaisgood et al , 2002(Swaisgood et al , 2004 and vocal signals (Charlton et al 2010), which may recruit males and incite competition, ensuring that the female mates with the best available male (Cox and Le Boeuf 1977).…”
Section: Introductionmentioning
confidence: 98%
“…Among such species, there have been many studies on female mate choice for male phenotype, because this promotes intersexual selection (Andersson 1994). Female mate choice for territory characteristics should also facilitate sexual selection by promoting male-male competition and indirect mate choice (Wiley and Poston 1996). However, female mate choice based on territory quality is less well studied owing to the difficulty of measuring territory quality in species with all-purpose territories containing many resources that are difficult to quantify (e.g., vegetation type and density, perch site, food, and nest site; Searcy and Yasukawa 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Such cases are called indirect mate choice (Wiley and Poston 1996). Indirect mate choice produces assortative mating in the same fashion as in direct mate choice, and it is widely accepted that indirect mate choice and male coercive behavior coevolved (Wiley and Poston 1996). Yamanoi et al (2006) suggested a possibility of indirect mate choice in this species, in which, by delaying copulation, females may exploit male-male competition to choose dominant males.…”
Section: Discussionmentioning
confidence: 98%
“…So, an individual indirectly chooses its own mate by setting the conditions for competition. Such cases are called indirect mate choice (Wiley and Poston 1996). Indirect mate choice produces assortative mating in the same fashion as in direct mate choice, and it is widely accepted that indirect mate choice and male coercive behavior coevolved (Wiley and Poston 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation